When Knowing What Is Just and Being Committed to Achieving it Is Not Enough. Issue 5 (22nd December 2021) - Buchanan, Allen
ABSTRACT: In this article, I argue that overly‐optimistic beliefs about how much progress toward justice has been made and overly‐pessimistic beliefs about what progress toward justice can be made can both help perpetuate injustices. Further, such beliefs can help perpetuate injustices even if those who hold them have a firm grasp of the correct principles of justice, a robust commitment to realize them, and the political influence to make their commitment effective. I also argue that when mistaken beliefs about justice of either sort are embedded in ideologies, they are an especially serious obstacle to moral progress. Finally, I conclude that ideologies can help perpetuate injustices even if they do not 'mask' them, if they include either overly‐optimistic or overly‐pessimistic beliefs about progress toward justice.